(untitled) (Nonconventional Technologies Review, 2024)
Self-compacting concrete, as a performing material whose casting and compacting can be made without applying the vibration technique, due to the flowability properties that allow it to flow by its own mass, was produced and tested in several versions of the material composition. Flowability gives high structural homogeneity and allows fast concrete pouring rate in a shorter time. During the experiment, four experimental versions were tested successively using coal ash, metallurgical slag, limestone dust as well as a combination of fly ash-slag as cementitious materials, that partially replaced Portland cement. Also, a water-reducing additive (polycarboxylate ether) was added in different ratios. Aggregates were chosen at low particle size (fine sand below 2 mm and granite gravel less than 12 mm). Mixing the materials together with the working water led to obtaining the paste with excellent flowability properties. The consolidated concrete had compactness and homogeneity and the mechanical characteristics were comparable to those of traditionally made concrete. Except for the remarkable flow characteristics of the paste, in this experiment it was proven that the compression strength of self-compacting concrete can reach very high values (after 28 days) of up to 60.4 MPa.